2022
DOI: 10.1186/s12915-021-01208-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic genetic differentiation drives the widespread structural and functional convergent evolution of snake venom proteinaceous toxins

Abstract: Background The explosive radiation and diversification of the advanced snakes (superfamily Colubroidea) was associated with changes in all aspects of the shared venom system. Morphological changes included the partitioning of the mixed ancestral glands into two discrete glands devoted for production of venom or mucous respectively, as well as changes in the location, size and structural elements of the venom-delivering teeth. Evidence also exists for homology among venom gland toxins expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 195 publications
5
31
0
Order By: Relevance
“…In addition, CTLs of front-fanged snakes have been shown to evolve rapidly [ 47 ]. Recently, Xie et al [ 48 ] found extensive duplication of novel dimeric CTLs genes unique to H. leopardinus . The novel CTLs found in H. leopardinus were shown to be under positive selection, but the distribution of these CTLs across the genus Helicops is currently unknown [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, CTLs of front-fanged snakes have been shown to evolve rapidly [ 47 ]. Recently, Xie et al [ 48 ] found extensive duplication of novel dimeric CTLs genes unique to H. leopardinus . The novel CTLs found in H. leopardinus were shown to be under positive selection, but the distribution of these CTLs across the genus Helicops is currently unknown [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Xie et al [ 48 ] found extensive duplication of novel dimeric CTLs genes unique to H. leopardinus . The novel CTLs found in H. leopardinus were shown to be under positive selection, but the distribution of these CTLs across the genus Helicops is currently unknown [ 48 ]. A previous study of H. angulatus found its venom lacked hemorrhagic activity, which is typically associated with SVMPs and CTLs [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, FX activation in P. volcanicum represents a third independent evolution of this trait within American pit-vipers. Underscoring the usefulness of this trait in prey capture, FX activation has evolved convergently in diverse Afro-Asian snake lineages such as the Daboia/Macrovipera/Montivipera viperid clade, viperid species Bitis worthingtoni , viperid genus Cerastes , viperid genus Echis , lamprophiid genus Atractaspis , and colubrid genus Rhabdophis [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. In contrast to FX activation being previously widely known as a convergent trait, Factor VII activation by snake venom has only previously been known for the Australian elapid clade of Oxyuranus + Pseudonaja [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only P. dunni was observed to inhibit thrombin, producing a significant delay in clotting time within the thrombin-inhibition assay ( Figure 4 ). Future work is required to ascertain which toxin types are responsible for inhibiting the clotting factors, with characterized inhibitors of clotting enzymes in viperid-snake venoms such as kunitz peptides, the alpha–beta covalently-linked dimeric-form of lectin toxins, and Group II phospholipase A 2 toxins [ 35 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three-finger toxins exhibit a postsynaptic neurotoxic activity as antagonists of nicotinic acetylcholine receptors ( Bourne et al, 2005 ), muscarinic acetylcholine receptors ( Chung et al, 2002 ), adrenergic receptors ( Rajagopalan et al, 2007 ), and GABA receptors ( Rosso et al, 2015 ). Recently, a molecular phylogenetic study has reported the presence of a three-finger toxin from M. monspessulanus that was very similar to the related Psammophis subtaeniatus , but also to the very neurotoxic elapid species Naja kaouthia ( Xie et al, 2022 ). Therefore, an ongoing study on the venom gland transcriptomic analysis of M. monspessulanus monspessulanus is needed to clarify and identify the toxin genes produced by this species and to provide greater insight into the venom composition and mode of action of this venom.…”
Section: Discussionmentioning
confidence: 99%